Cognitive big data intelligence with a metaheuristic approach - Mishra, Sushruta; Tripathy, Hrudaya Kumar; Mallick, Pradeep Kumar, 1984-; Sangaiah, Arun Kumar, 1981-; Chae, Gyoo-Soo, 1968- (Cognitive data science in sustainable computing., 2021)
Cognitive Big Data Intelligence with a Metaheuristic Approach presents an exact and compact organization of content relating to the latest metaheuristics methodologies based on new challenging big data application domains and cognitive computing. The combined model of cognitive big data intelligence with metaheuristics methods can be used to analyze emerging patterns, spot business opportunities, and take care of critical process-centric issues in real-time. Various real-time case studies and implemented works are discussed in this book for better understanding and additional clarity. This book presents an essential platform for the use of cognitive technology in the field of Data Science. It covers metaheuristic methodologies that can be successful in a wide variety of problem settings in big data frameworks. --